Holding their breath : how the Allies confronted the threat of chemical warfare in World War II - Dorsey, M. Girard, 1971- (Battlegrounds (Ithaca, N.Y.), 2023)
"Beginning with the interwar period and concluding with the defeat of Japan, this book examines diplomatic, legal, military, and social issues the Western Allies (Great Britain, the United States, and Canada) confronted when they faced the threat and considered the use of chemical weapons during World War II"--